Quality and Purchase Intention Perceived towards Low Cost Energy-Saving Cars - Setiawan, Edhie Budi (STMT Trisakti, 2015)
Low cost car does not mean having low quality. This is the assumption that the producers or sellers of especially energy-saving car want to emphasize. This research on the desire and expectation of every car producer and dealer in Indonesia who tries to be perceived as having the best quality on their consumers mind and on the increase of consumer purchase intention is carried out using a qualitative method as well as the concept of perceived service qualityâwhich shows the difference between bibliographic study and the actual condition. Keywords: Low cost car, perception on quality, purchase intention